Proposed new interior design scheme of Zoo Taiping Education Centre at Jalan Taman Tasik Taiping, 34000 Taiping, Perak Darul Ridzuan / Farah Amalina Jamal - Jamal, Farah Amalina (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of diploma in interior design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design.The project that had been chosen for the final project is to proposed a new interior design of ZOO TAIPING EDUCATION CENTER FOR ZOO TAIPING at Jalan Taman Tasik Taiping, 34000,Taiping,Perak Darul Ridzuan. This proposed education center is to attract users,mostly on kids to experience themselves at this education center,at the same time to aims to spread knowledge on animal behaviour, animal handling and on public safety in regards to animal encounters. The target market for the users of this education center is kids from 6 to 12 years old. It is also a place where students can conduct their research projects for their certificate, diploma .degree,masters,PHD from different area of interests.every spaces that proposes would match with the customer’s need and it could give comfort to them while attending this education center. Concept and image that had been chosen must be suitable with the clients as both of it will reflect the client itself,but at the same time,it would give a positive impact and to increase the faith in the customers and the workers in the zoo taiping education center. Connected to that,the chosen design style for zoo taiping education center is based on modern and fun design,goes all the way with the client’s needs as they want the education center to have the fun look and at the same time would attract the customer with different image that they would only get in zoo taiping education center. Before get a desired design that is suitable with the client’s needs,some data analysis should be done where these analysis is on types of services offered, spaces to be concluded in the proposed area .operation time and informations about other education center that used the same system in management,as the proposed education center.some of the gained information of the study is through interviews, printed media, internet, observation,and through the result from the case study either locally or internationally.